(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study examined the innovative transformation embedded in the design of the 2023 Education Curriculum Framework implemented in Zambia. This systematic review examined the 2023 Zambia Education Curriculum Framework (2023 ZECF) and interview with key stakeholder in the development of the Curriculum to explore the innovative transformation embedded in it. Key innovations transformation included the integration of cross-cutting themes, the education that focus on education for sustainability development, learner-centered pedagogy, integration of soft and technical skills, decentralized curriculum contextualization, digital and blended learning modalities, community and industry partnership inclusion, continuous, formative, and criterion-referenced assessment, inclusive and differentiated learning strategies, global citizenship education and categories of special education needs in the 2023 education curriculum. Through qualitative analysis of policy documents, stakeholder interviews, and classroom observations, the study identifies challenges in implementation including teacher preparedness, resource limitations, and community engagement and proposes strategic recommendations for effective curriculum delivery. The findings underscore the curriculum’s potential to equip Zambian learners with critical thinking, creativity, collaboration, and communication skills essential for national development and global competitiveness.